John Keats - White, R. author. aut Link
X, 260 p.
Keywords: At the heart of this 'Literary Life' are fresh interpretations of Keats's most loved poems, alongside other neglected but rich poems. The readings are placed in the context of his letters to family and friends, his medical training, radical politics of the time, his love for Fanny Brawne, his coterie of literary figures and his tragic early death.